Finance, social value, and the rhetoric of GDP - Jacob Assa (Finance and Society, 2018)
The global financial crisis is usually seen as a failure of neoclassical economic theory and neoliberal policy, but it also represented an epistemological failure. Forecasters who missed the crisis neglected to include the financial sector in their models, while aggregate indicators such as GDP failed in spite (or perhaps because) of their heavy emphasis on financially driven growth. In contrast to both critics and proponents of GDP who see it as a purely statistical measure, this article argues that GDP is in fact a form of numerical rhetoric. Political messages in such estimates were explicit until the early twentieth century, but have since become implicit in hidden assumptions. To uncover the narratives built-in to GDP's view of finance, the article conducts a thought-experiment comparing GDP with two counterfactual indicators corresponding to historical views of finance as either non-productive or an actual cost to society. The analysis shows how changing this single assumption leads to very different narratives regarding the class-balance of workers vs. capitalists, the relative importance of consumption, and the extent of space that exists for public policy to influence the economy. The article concludes with some thoughts on making the implicit assumptions in GDP explicit, and opening up the debate to the broader public in a transparent way.